Satisfactory short-term outcomes of totally laparoscopic ileostomy reversal compared to open surgery in colorectal cancer patients - Xu, Zheng; Luo, Shou; Su, Hao; Liang, Jianwe; Liu, Qian; Wang, Xishan; Jin, Weisen; Zhou, Haitao (Frontiers in Surgery, 2023)
Background Recently, totally laparoscopic (TLAP) surgery has suggested its potential on ileostomy reversal. This study aimed to compare the short-term outcomes between TLAP and traditional open ileostomy reversal. Patients and methods From September 2016 to September 2021, 107 eligible patients underwent TLAP (n = 48) or open (n = 59) loop ileostomy reversal were retrospectively enrolled. Surgical parameters, postoperative recovery and complications were identified and compared between TLAP technique vs. open surgery. Results The operation time and estimated blood loss showed no obvious difference between TLAP and open group. However, TLAP reversal significantly decreased the incision length (4.5cm vs. 6cm, P < 0.001). Furthermore, patients underwent TLAP surgery showed quicker first ground activities (1 day vs. 2 days, P < 0.001), faster first flatus passage (2 days vs. 3 days, P = 0.004) and shorter postoperative stay (5 days vs. 7 days, P = 0.007). More importantly, postoperative complications were significantly reduced after TLAP reversal (3 cases vs. 10 cases, P = 0.026). Further logistic regression analyses also indicated the TLAP technique was associated with lower incidence of complications (OR=3.316, CI, 1.118–9.835; P = 0.031). Conclusions TLAP surgery is competitive in promoting postoperative recovery as well as reducing complications compared to the traditional open ileostomy reversal.